Microfluidic Genotyping by Rapid Serial PCR and High-Speed Melting Analysis. (1st October 2014) - Sundberg, Scott O; Wittwer, Carl T; Howell, Renée M; Huuskonen, Jarkko; Pryor, Robert J; Farrar, Jared S; Stiles, Heather M; Palais, Robert A; Knight, Ivor T
Abstract: BACKGROUND: Clinical molecular testing typically batches samples to minimize costs or uses multiplex lab-on-a-chip disposables to analyze a few targets. In genetics, multiple variants need to be analyzed, and different work flows that rapidly analyze multiple loci in a few targets are attractive. METHODS: We used a microfluidic platform tailored to rapid serial PCR and high-speed melting (HSM) to genotype 4 single nucleotide variants. A contiguous stream of master mix with sample DNA was pulsed with each primer pair for serial PCR and melting. Two study sites each analyzed 100 samples for F2 (c.*97G>A), F5 (c.1601G>A), and MTHFR (c.665C>T and c.1286A>C) after blinding for genotype and genotype proportions. Internal temperature controls improved melting curve precision. The platform's liquid-handling system automated PCR and HSM. RESULTS: PCR and HSM were completed in a total of 12.5 min. Melting was performed at 0.5 °C/s. As expected, homozygous variants were separated by melting temperature, and heterozygotes were identified by curve shape. All samples were correctly genotyped by the instrument. Follow-up testing was required on 1.38% of the assays for a definitive genotype. CONCLUSIONS: We demonstrate genotyping accuracy on a novel microfluidic platform with rapid serial PCR and HSM. The platform targets short turnaround times for multiple genetic variants in up to 8 samples. It is also designed to allow automatic and immediate reflexive or repeat testing depending on results from the streaming DNA. Rapid serial PCR provides a flexible genetic work flow and is nicely matched to HSM analysis.